2022
DOI: 10.1002/cphc.202100833
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation and Conductance Modulation of a Metal‐Molecule‐Metal Junction via Extra Acid Addition

Abstract: One important prerequisite for the fabrication of molecular functional device strongly relies on the understanding the conducting behaviors of the metal-molecule-metal junction that can respond to an external stimulus. The model Lewis basic molecule 4,4'-(pyridine-3,5-diyl)dibenzonitrile (DBP), which can react with Lewis acid and protic acid, was synthesized. Then, the molecular conducting behavior of DBP, DBP-B(C 6 F 5 ) 3 , and DBP-TfOH (DBP-B(C 6 F 5 ) 3 , and DBP-TfOH were produced by Lewis acid and proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…For the molecular wires terminated by the pyridine anchoring group, the dominated charge carriers are electrons. 31,32 Fig. 4b illustrates the transmission spectra across the molecular junctions composed of p-Co-p, p-Co-m, m-Co-m and their alkynyl counterparts at V = 0 V. It was found that the conductance of molecular wires with meta-linked pyridine anchors decreased.…”
mentioning
confidence: 99%
“…For the molecular wires terminated by the pyridine anchoring group, the dominated charge carriers are electrons. 31,32 Fig. 4b illustrates the transmission spectra across the molecular junctions composed of p-Co-p, p-Co-m, m-Co-m and their alkynyl counterparts at V = 0 V. It was found that the conductance of molecular wires with meta-linked pyridine anchors decreased.…”
mentioning
confidence: 99%
“…对于每个模型, 分子嵌入 两个金电极的空穴位点, Au-Au 键长度为 0.288 nm [24] , 硫原子与金等三角形中心之间的最佳距离采用 0.230 nm [17] . 同时采用密度泛函结合非平衡格林函数(DFT+ NEGFs)方法优化分子结的几何结构并计算相应分子结 的电子输运性质 [25][26] . 其中, 金电极采用 3×3 Au(111) 周期性模型, 广义梯度近似(GGA-PBE)方法评估电子交 换和相关能.…”
unclassified